Faktor Risiko Kejadian Diabetes Mellitus Tipe 2 pada Pasien Rawat Jalan di RSUD Kabupaten Buton Tahun 2023 - Nurul Amalliah; Febriana Muchtar; Jusniar Rusli Afa (Universitas Pahlawan Tuanku Tambusai, 2024)
Abstract : Diabetes mellitus is a degenerative disease that poses a significant threat to human health due to insufficient insulin production in the pancreas or when the body fails to effectively utilize the insulin. Diabetes mellitus is diagnosed based on blood glucose levels and the type 2 diabetes is the most prevalent types of diabetes. This research was conducted to identify the risk factors associated with the prevalence of type 2 diabetes mellitus among outpatients at Buton District General Hospital in 2023. This case-control research involved all 402 outpatients diagnosed with type 2 diabetes mellitus at Buton District General Hospital from January to October 2023 as research population, from which 120 patients were purposively selected as samples. Based on the findings of this research, several risk factors were identified: age (OR=4.677 and p=0.000), obesity (OR=3.000 and p=0.006), physical activity (OR=4.677 and p=0.000), and stress (OR=2.286 and p=0.043). In addition, several variables such as gender (OR=0.606 and p=0.258) and dietary pattern (OR=0.360 and p=0.011) appeared as factors that lower the prevalence of the disease. In conclusion, age, obesity, stress, and physical activity are risk factors for the prevalence of type 2 diabetes mellitus among outpatients at Buton District General Hospital in 2023, while gender and dietary pattern serve as protective factors.